2013
DOI: 10.1002/aenm.201300543
|View full text |Cite
|
Sign up to set email alerts
|

Cu‐Rich Precursors Improve Kesterite Solar Cells

Abstract: A precursor‐annealing process based on a Cu‐rich precursor that has a maximum power conversion efficiency of 7.5% for pure selenide kesterite cells is presented. The Cu‐rich step is beneficial for the transport properties. Nanometer‐sized domains of ZnSe are found in all films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 22 publications
3
59
1
Order By: Relevance
“…Mousel et al [20] attributed this observation to the Cu-rich nature of the precursor. It was shown that due to the incorporation of Sn the overall composition (measured by EDX) shifts from Cu-rich to Cu-poor.…”
Section: Absorber Filmsmentioning
confidence: 97%
See 4 more Smart Citations
“…Mousel et al [20] attributed this observation to the Cu-rich nature of the precursor. It was shown that due to the incorporation of Sn the overall composition (measured by EDX) shifts from Cu-rich to Cu-poor.…”
Section: Absorber Filmsmentioning
confidence: 97%
“…In a previous work [20] the present authors detected a Cu-rich surface on the Cu-rich precursor by SIMS depth profiling and found indications for the formation of a Cu-Se phase. However, the distribution of this phase on the sub-micrometer scale was not studied in detail.…”
Section: Precursor Filmsmentioning
confidence: 99%
See 3 more Smart Citations